Factors related to prevalence of depression in Türkiye: a population-based study - Yıldız, Nadire Gülçin; Aydın, Kemal; Aydın, Halide Z.; Phiri, Yohane V.A.; Yıldız, Hatice (My University, 2024)
Objective: This study aims to determine the prevalence of depressive symptoms in the adult population in Türkiye and to examine the relationship of depression with socio-demographic and behavioral variables and chronic diseases. Method: This sturdy utilized data from the 2019 Turkey Health Survey. The Patient Health Questionnaire Depression Module (PHQ-8) was employed to assess depressive symptoms in the survey. Based on the analysis using the diagnostic algorithm of the PHQ-8, from a total of 17084 people aged 15+ years old who were, we selected 6.4% individuals with depressive symptoms. Then, we randomly selected 1101 individuals without depressive symptoms, comprising of a total of 2202 individuals as the study sample. We assessed the factors associated with depressive symptoms using multivariate logistic regression analyses. Results: The risk of developing depressive symptoms increased with age. Women were more likely to report depressive symptoms. Education, physical activity, and marital status were negatively correlated with reporting depressive symptoms. Further, social support was a protective factor to report depressive symptoms. The presence of chronic diseases was positively associated with depressive symptoms. Conclusion: The results showed that point and annual prevalence of depressive symptoms were high. The findings provide a basis for further studies to explore the factors associated with a higher prevalence of depressive symptoms in Türkiye. Our findings could serve as a reference to monitor depression in the country, as well as help in the planning of health resource and identify high risk segments of the population.
Keywords: Coronary Heart Disease; Depression; Diabetes; Hypertension; Low Back Pain; Oslo-3 Social Support Scale (OSSS-3); Physical Activity Questionnaire (IPAQ); Socioeconomic and Demographic Factors